Prevention of endocarditis caused by transient bacteremia after tooth extraction - Sasaki, Jiro; Kaneko, Akihiro (Japanese Journal of Chemotherapy, 2001)
We studied the prevention of bacterial endocarditis, i. e., lowering the incidence of transient bacteremia by administering antibiotics prior to tooth extractions. In the U. S., the American Heart Association (AHA) publicly announced in 1977 a regimen of preventive administration. The latest was published in the JAMA (1997). The regimen recommends the administration of antibiotics by venous infusion to high-risk patients and oral administration to moderate-risk patients. Our was to determine form a regimen more suitable to the Japanese than the AHA's as a guide to dental practitioners for chemoprophylaxis for moderate-risk patients in oral antibiotics administration. (1) Healthy patients. Subjects were the 47 volunteers from among doctors and nurses who work for the Tokai University. They had venous blood (15 mL) taken immediately after tooth extraction without antibiotics administration. The positive rate of blood culture was 69.2%(35/47). Streptococcus milleri and Peptostreptococci were the top 2 strains detected. (2) High-risk patients Subjects had a history of valve replacement or bacterial endocarditis. They were administered antibiotics by venous infusion prior to tooth extractions. Cases numbered 236 patients and 8 antibiotic agents were tested. Carbapenems showed the lowest positive rate. (3) Moderate-risk patients We tested 4 commercially available antibiotics for oral administration obtained easily in Japanamoxicillin, faropenem, cefterampivoxil, and clarithromycin. Cases numbered 60 cases of amoxillin (500mg/dose), 45 for faropenem (400mg/dose), 14 for cefteram pivoxil (300mg/dose), and 16 for clarithromycin (600mg/dose). Amoxillin showed the lowest positive rate of 26.7%(16/60), followed by faropenem. Our recommendation based on the above experiment is that to lower the positive rate of blood culture after tooth extraction, dental practitioners should administer 500mg of amoxillin 61 minutes to 110 minutes before tooth extraction or 400mg of faropenem 70 minutes to 120 minutes before they start treatment.